Change in choroidal thickness and axial length with change in intraocular pressure after trabeculectomy. Issue 7 (13th March 2014) - Saeedi, Osamah; Pillar, Angelique; Jefferys, Joan; Arora, Karun; Friedman, David; Quigley, Harry
Abstract : Background/aims: We studied the change in choroidal thickness (CT) and axial length (AL) after intraocular (IOP) changes produced by trabeculectomy. Methods: Twenty-one eyes of 20 patients were studied preoperatively, and then postoperatively at 1 week, 1, 3, and 6 months. Variables measured included IOP, AL, keratometry, refractive error, central corneal thickness, and average CT in the posterior 6 mm centred on the fovea using enhanced depth imaging spectral domain optical coherence tomography (OCT). Results: OCT images in 17 eyes (58 images, preoperatively and postoperatively) were of sufficient quality to determine CT. In every patient, CT increased with IOP lowering postoperatively. For each 1 mm Hg decrease in IOP, there was a mean increase of 3.4 µm in CT (p<0.0001; univariate regression, 95% CI 2.5 to 4.3). This represented a CT increase of 1.7% per mm Hg decrease (p<0.0001; 95% CI 1.3 to 2.0%). AL decreased by 6.8 µm per mm Hg decrease in IOP (p<0.0001, univariate regression, 95% CI 4.9 to 8.6). Conclusions: The dynamic relationship between change in IOP and the state of sclera and choroid was confirmed by sequential measurements in postoperative trabeculectomy patients, providing estimates of the magnitude of choroidal swelling and scleral volume decrease with IOP lowering.